Quality of Work Life of Teaching Staff Working at a Higher Education Institution in Saudi Arabia: A Cross-sectional Study. Issue 45 (8th August 2019) - Subbarayalu, Arun Vijay; Al Kuwaiti, Ahmed
Abstract: A cross-sectional survey design was adopted to study the quality of work life (QoWL) of the teaching staff employed at a Saudi higher education institution, focusing on their ethnic backgrounds and the academic clusters in which they were employed. A total of 360 teaching staff were randomly selected using a two-stage cluster sampling method, and a self-structured quality of work life questionnaire was used to collect data. Statistical analysis was done using SPSS 19.0. The results indicated that 71% of the respondents were satisfied with their QoWL at Imam Abdulrahman Bin Faisal University (IAU), Saudi Arabia. A significant difference of opinion was observed among the teaching staff on two dimensions of QoWL, viz. 'working conditions' and 'psychosocial factors' ( p < 0.05). However, no significant difference was observed on other QoWL attributes, such as 'opportunity for training and development' and 'job satisfaction and job security' ( p > 0.05). Given that all public universities in Saudi Arabia are governed by regulations framed by the Ministry of education, this study provides important indicators to educational policy planners on understanding the QoWL of teaching staff employed in universities across Saudi Arabia.